Attachment Disturbances Delay Language Acquisition in Internationally Adopted Children. Issue 3 (2nd July 2016) - Jensen, Rachel M.; Helder, Emily J.; Gunnoe, Marjorie Lindner
ABSTRACT: Cross-sectional research on internationally adopted children has indicated an association between early attachment disturbances and language deficits. Raaska et al. (2013 ) have speculated that this relationship is likely bidirectional. In an attempt to elucidate the causal relationship between these two risk factors, the attachment disturbances and language skills of 44 internationally adopted children were assessed in a cross-lagged structural equation model. Greater attachment disturbances at wave 1 predicted less gain in language by wave 2. In contrast, language at wave 1 was not predictive of attachment disturbances at wave 2. These results suggest that early attachment problems may present an important risk for later language development and should be an immediate and primary focus of post-adoptive intervention for families adopting internationally.